THE INFLUENCE OF NUTRITION ON EDUCANIOL ACTIVITIES - Abdurashitova Sh. A.; Malikova G.S. (Journals Park Publishing, 2025)
This article highlights the importance of good nutrition for students, highlighting key aspects and providing recommendations to help them cope better and maintain well-being.
Keywords: Healthy lifestyle, students, rational nutrition, unhealthy nutrition, balance, metabolism.